Shared Dynamics of Food Decision-Making in Mother-Child Dyads - Ha, Oh-Ryeong; Bruce, Amanda S.; Killian, Haley J.; Davis, Ann M.; Lim, Seung-Lark (Frontiers in Psychology, 2021)
This study explored risk parameters of obesity in food decision-making in mother-child dyads. We tested 45 children between 8-12 years and their biological mothers to measure the decision weights of food health attributes, the decision weights of food taste attributes, self-regulated food decisions, and self-reported self-control scores. Maternal body mass index (BMI), and children’s BMI-percentiles-for-age were also measured. We found a positive correlation between children’s and their mothers’ decision weights of taste attributes in food decision-making. We also found a positive correlation between children’s BMI %iles and their mothers’ BMIs. Children with overweight/obesity demonstrated lower decision weights of health attributes and a lower percentage of self-regulated food decisions (i.e., resisting to eat tasty but unhealthy foods or choosing to eat not-tasty but healthy foods) than children with healthy weight. Our findings suggested that the decision weights of taste attributes and weight status shared similar patterns in mother-child dyads. Also, the findings suggested that establishing dynamics of unhealthy food-decision making may increase the risk of childhood obesity. Helping children to develop the dynamics of healthy food-decision making by increasing the importance of health while decreasing the importance of taste may promote resilience to susceptibility to unhealthy eating and weight gain.